Sources of the Nazi racial ideology - Herlinde Pauer-Studer (Mètode Science Studies Journal: Annual Review)
This is an extract from Pauer-Studer, H. (2020). Justifying injustice. Legal theory in Nazi Germany. (Cambridge University Press, 2020, pp. 117–124). The author analyses the adaptation of German law to the political goals of National Socialism.